2011
DOI: 10.1590/s0102-86502011000100009
|View full text |Cite
|
Sign up to set email alerts
|

Subtotal laparoscopic splenectomy in rats with preservation of the inferior pole

Abstract: Purpose:To evaluate the feasibility and safety of subtotal splenectomy by laparoscopy with inferior pole preservation and to determine the viability of the splenic remnant. Methods: Twenty male Wistar rats weighing between 365 g and 474 g (mean 417.92 ± 36.15g SD) were operated and randomly assigned to two groups : Group 1 rats were killed on postoperative day 10 (n = 10), and Group 2 on the postoperative day 80 (n = 10). Both the inferior splenic pole and the superior part of the spleen, which was used as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Studies with different experimental models showed significant changes in the lipid profile of the splenectomized animals 1,6,7,9,[19][20][21][22] . However, when part of the spleen is preserved, its viability is maintained [23][24][25] closer to the metabolic profile of humans due to the strong controversies and high morbidity and mortality rates caused by complications from the atherosclerotic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with different experimental models showed significant changes in the lipid profile of the splenectomized animals 1,6,7,9,[19][20][21][22] . However, when part of the spleen is preserved, its viability is maintained [23][24][25] closer to the metabolic profile of humans due to the strong controversies and high morbidity and mortality rates caused by complications from the atherosclerotic disease.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that both distal pancreatectomy with splenectomy or splenectomy alone can be safely performed and such resection procedures require the development of surgical skills for dealing with rats 17,18 . The two rat's death because of gastric perforation and intra-abdominal bleeding occurred early, during or on the day after the laparoscopic procedures, but the mortality rate was significantly reduced as soon as the learning curve ended.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Experimental rat models of laparoscopic surgery have been described previously 5,6 . However, laparoscopic surgeries, especially intracorporeal anastomosis, are difficult to perform in rat models, which require special materials for laparoscopic microsurgery [7][8][9] .…”
Section: Discussionmentioning
confidence: 99%